Degradation of metallophtalocyanine dye by combined processes of electrochemistry and photoelectrochemistry - Osugi, M. E.; Umbuzeiro, G. A.; Anderson, M. A.; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2005)
Photoelectrocatalytic degradation of metallophtalocyanine reactive dye (turquoise blue 15) was performed using a Ti/TiO2 thin film photoanode prepared by sol-get method. Hundred percent of color removal and almost complete mineralization (95% at pH 2 and 85% at pH 8) where achieved after 6 h of photolectrocatalytic oxidation of 2.5 x 10(-5) mol L-1 AT15 dye in Na2SO4 mol L-1 under E = +1.2 V versus SCE. The method limitation occurs at dye concentration higher than 4 x 10-5 mol L-1, where the degradation rate becomes markedly slower. An important improvement in color removal and TOC reduction for 1 x 10(-3) mol L-1 metallophtalocyanine dye was achieved using a combined process. After 4 h of potential controlled electrolysis at -1.2 V on a cathode of platinum followed by 6 h of photoelectrocatalytic oxidation leads to 100% of color removal and 83% of TOC decay and eletrodeposition of 69% of the released copper originally presented as copperphtalocyanine complex, by electrodeposition on the cathode without any other treatment. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: cooperphtalocyanine dye; photoelectrocatalytic oxidation; Ti/TiO2 electrodes